DYSTOCIA DUE TO DICEPHALUS MONOSTOMUS MONSTER IN A JERSEY CROSS BRED HEIFER - RAVIKUMAR, K; KRISHNAKUMAR, K; KUMARASEN, A; CHANDRAHASAN, C (The Indian Journal of Animal Reproduction, 2023)
Dystocia due to dicephalus monostomus monster was relieved by cesarean section in a jersey cross bredheifer.
Keywords: Dicephalus; Monostomus; Monster; Jersey; Heifer; Dystocia